An evaluation of a positive psychology programme used to support potentially vulnerable secondary school students to enhance their well-being, self-efficacy, resilience and related behaviours - Duffin, Amy R. (2019)
Traditional mental health support in schools focuses upon emotional difficulties rather than preventatively developing skills and enhancing resilience (McGrath, 2010). Positive psychology approaches support children to be mentally healthy through emphasising strengths (McGrath, 2010). There is however, a need to measure the impact and outcomes of positive psychology programmes in schools to build an evidence base (McGrath, 2010) and educational psychologists can contribute to this (Shute, 2012).